South-South Cooperation and the 2030 Agenda. The experience of Colombia’s International Cooperation Agency - Escallón, Myriam; Gamba, Camilo; García, Juana; Roa, Luis Ángel; Rodríguez, Daniel (Revista Española de Desarrollo y Cooperación, 2023)
Having taken an active role in designing the 2030 Agenda, the Government of Colombia has sought to strengthen its knowledge management and South-South Cooperation (SSC) to help achieve the SDGs. By analyzing the SSC Toolkit and the Saber Hacer Colombia program, the authors comment on the role of SSC and the knowledge management in the global agendas.
Keywords: Knowledge management; Technical cooperation; 2030 Agenda